Cost‐Effectiveness Analysis of Peripheral Nerve Field Stimulation as Add‐On Therapy to Spinal Cord Stimulation in the Treatment of Chronic Low Back Pain in Failed Back Surgery Syndrome Patients. Issue 5 (18th August 2019) - van Gorp, Eric‐Jan J.A.A; Adang, Eddy M.M.; Gültuna, Ismail; Hamm‐Faber, Tanja E.; Bürger, Katja; Kallewaard, Jan Willem; Schapendonk, Johannes W.C.L; Vonhögen, Leon; Bronkhorst, Ewald; Teernstra, Onno P.; Vissers, Kris C.P.
Abstract : Objective: Presently, there is only limited evidence about the cost‐effectiveness of peripheral nerve field stimulation (PNFS) and no evidence to date on the cost‐effectiveness of PNFS as an add‐on therapy to spinal cord stimulation (SCS). In a multicenter randomized controlled trial, PNFS as add‐on therapy to SCS demonstrated clinical effectiveness in treating chronic low back pain in failed back surgery syndrome (FBSS) patients. We report here the cost‐effectiveness of PNFS as additional therapy. Materials and Methods: Cost‐effectiveness analysis was performed from a health‐care perspective using the general principles of cost‐utility analysis, using empirical data from our multicenter randomized controlled trial on the effectiveness of hybrid SCS + PNFS on low back pain in FBSS patients, who were back pain non‐responders to initial SCS‐therapy, over a time‐horizon of three months. Outcome measures were costs and quality‐adjusted life‐years (QALYs). Cost and QALYs were integrated using the net monetary benefit (NMB). Differences in costs, effects, and NMB were analyzed using multilevel regression. Uncertainty surrounding the NMB was presented by cost‐effectiveness acceptability curves. Results: A total of 52 patients implanted with both SCS and PNFS, randomly assigned to a group with PNFS either activated or inactive, completed the controlled part of the study. With mean total costs for the SCS + active PNFS group of €1813.86 (SD €109.78) versus €1103.64 (SD €123.43) for the SCS + inactive PNFS group at three months, we found an incremental cost‐utility ratio of €25.311 per QALY gained and a probability being cost‐effective of more than 80% given a willingness to pay for a QALY of about €40.000. Conclusions: From a Dutch national health‐care context, when the willingness to pay threshold is up to 60.000 Euros per QALY, PNFS as an add‐on therapy to SCS for the treatment of low back pain in FBSS patients has a high probability of being cost‐effective.